GENETICA, ECOLOGIA Y EVOLUCION DE LAS ESPECIES CHILENAS DEL GENERO RHAGOLETIS (DIPTERA: TEPHRITIDAE) (Acta Entomológica Chilena, 2022)
This paper discuss the results of evolutionary biology of species of Rhagoletis known from Chileunder the general frame of the theory of speciation.Most chilean-species are endemic, with the solé exception of R. tomatis which reaches SouthPerú in its distribution. These species belong to the group nova, and are different from the rest ofneotropical species by the presence of an apomorphic trait in the female ovipositor. Moreover, in oneof them, R. conversa, has emerged a probable atavie character, detected only in the past 10 years,which appears to constitute a paradigm of a microevolutive process in action.All the studied species with the solé exception of R . tomatis show a pupal diapause which varíesaccording lo some ecological factors, such as the availability of host fruits where oviposit. Thisdiapause would also be controled by genetic factors, photoperiod, lemperature and relative humidity.The genetic studies in the chilean especies of central distribution (R. conversa y R. nova) showthat changes at the level of structural genes are minimun during the evolutive process in thesespecies, and that speciation would occur in sympatry and rather during relatively short periods ifcompared with the speciation process in allopatry. Nevertheless in R. tomatis the allopatricspeciation is the principal factor of significative differentation in relation of the other congenericchilean species.
Keywords: Rhagoletis, Genetics, Ecology, Evolution